Mesoscopic phenomena in solids - Altshuler, B. L.; Lee, P. A. (Patrick A.), 1946-; Webb, R. A. (Richard Alan) (Modern problems in condensed matter sciences, 1991)
The physics of disordered systems has enjoyed a resurgence of interest in the last decade. New concepts such as weak localization, interaction effects and Coulomb gap, have been developed for the transport properties of metals and insulators. With the fabrication of smaller and smaller samples and the routine availability of low temperatures, new physics has emerged from the studies of small devices. The new field goes under the name "mesoscopic physics" and has rapidly developed, both experimentally and theoretically. This book is designed to review the current status of the field. Most of the chapters in the book are devoted to the development of new ideas in the field. They include reviews of experimental observations of conductance fluctuations and the Aharonov-Bohm oscillations in disordered metals, theoretical and experimental work on low frequency noise in small disordered systems, transmittancy fluctuations through random barriers, and theoretical work on the distribution of fluctuation quantities such as conductance. Two chapters are not connected directly to the mesoscopic fluctuations but deal with small systems. They cover the effects of Coulomb interaction in the tunneling through the small junctions, and experimental results on ballistic transport through a perfect conductor